Effective supervisory approach in enhancing postgraduate research studies - Zainal Abiddin, Norhasni; Ismail, Affero; Ismail, Azahari (Center for Promoting Ideas, 2011)
Supervision is defined as intensive, interpersonally focused one-to-one relationship between the supervisor and the student. Supervisor is designated to facilitate the student’s academic development either in terms of courseworks or research project. This paper address supervision as a complicated process that is influenced by many factors, including the social setting, the personalities of the supervisor and the student, the relationship that develops between them, the expertise of the supervisor, and the problems varied among students. Approach of supervisory inputs that have influenced supervision will be discussed, while the importance of relationship skills in supervision will be highlighted. The paper’s thrust will be to disscuss the important inputs in supervision process and to highlight the social nature of the interaction between supervisor and student. It is hoped to assist the institution to identify and address implementation issues related to postgraduate supervision. The major contribution of this review is the guideline for effective supervision in enhancing postgraduate research studies.